ASSESMENT OF HEAVY METAL POLLUTION (Hg, Pb, Cd) IN THE PASURUAN SEA: STATUS AND COUNTERMEASURES - Dina, Karina Farkha; Herawati, Endang Yuli; Arfiati, Diana; Anugerah, Putri (Indonesian Fisheries Research Journal, 2025)
Pasuruan Regency is a major industrial center in Indonesia where their heavy metal industrial waste accompanied by  , household waste, and agricultural activities polluted  Pasuruan waters. The purpose of this study was to determine the status of heavy metal pollution in the Pasuruan sea in the coastal areas of Kraton, Lekok and Nguling and to find out how to overcome it. The survey method was used in this study to analyze the levels of heavy metals (Hg, Pb, Cd) in the waters and calculate the water pollution status based on the pollution index and water quality. Water sampling is carried out at a depth of between 2-15 meters at 3 stationary lift nets (Bagan tancap) at each location. The results showed that the highest levels of heavy metals were found in Lekok waters. The results of the calculation of the pollution index (IP) show that Lekok water has a heavy pollution status for all types of heavy metals (Hg, Pb, Cd). The pollution status in Nguling and Kraton waters based on the Hg and Cd pollution index is classified as heavily polluted. Meanwhile, heavy metal levels of Pb still meet water quality standards. The results of measurements of temperature, pH, dissolved oxygen, salinity, and current velocity are classified as optimum for aquatic biota. Based on the research results, it is known that there are areas of Pasuruan waters that are heavily polluted. Therefore, better water quality management is needed to meet the needs of biota by planting Rizhophora mucronata mangroves.